AKIBAT HUKUM APARATUR SIPIL NEGARA YANG MELAKUKAN KEJAHATAN BERHUBUNGAN DENGAN JABATAN DI TINJAU DARI UNDANG – UNDANG NOMOR 5 TAHUN 2014 TENTANG APARATUR SIPIL NEGARA (STUDI KASUS : PUTUSAN PENGADILAN TATA USAHA NEGARA NOMOR37/G/2018/PTUN.PDG). - Boby Harnendi Putra (Fakultas Hukum Universitas Tarumanagara, 2021)
Aparatur Sipil Negara is a Indonesian government institution that was created with the aim of running the government to realize the ideals of the nation, Aparatur Sipil Negara consists of civil servants and government employees with work agreements (PPPK), behind its implementation function as the assistance of the Indonesian state, on the other hand, Aparatur Sipil Negara is not immune from criminal acts, as for the criminal acts discussed are crimes related to positions, crimes committed by the state civil Apparatus have a direct impact on the community, it is like a stalled development, slowing economy and much more, Aparatur Sipil Negara who is proven legally and convincingly to commit a crime related to the position, will be immediately given legal sanctions,as for the legal sanctions, they can be in the form of sanctions in accordance with Kitab Undang – Undang Hukum Pidana until Undang – Undang Tindak Pidana Korupsi, further information regarding the sanction of dismissal that will be imposed on Aparatur Sipil Negara who commits a crime of office crime that will be carried out by a government agency like President, Minister, Governor, also Regent. Does not end there, Komisi Aparatur Sipil Negara and Badan Kepegawaian Negara also participate in making proposals as well as supervising Aparatur Sipil Negara working in the government.